Implications des consultants qualité dans l’institutionnalisation du nouveau mode de pilotage du système éducatif chilien - Manuel González Carpanetti; Gilles Monceau (Éducation et Socialisation)
The application of the principles of New Public Management to the school institution produces the emergence of new professions. Chili, since 2003, was one of the first countries to generalize certification procedures for its schools and thus create a new area of professional activity, that of quality consultation. The research to be reported here relates to the experience of a group of chilean quality consultants. These consultation practices, the tools they mobilize and the institutional transformations they produce constitute a new ground for education research. Although there are many publications on the international dissemination of quality management in education systems, there is no specific work on the work done by consultants. The results of the research show how these consultants mobilize the technical objects that constitute their « toolbox » to influence the involvement of school leaders and their teams in the process of institutionalizing the piloting through the quality of the education system. It is therefore also a question of showing how the support of schools towards quality certification affects the implication of the consultants themselves.